2002
DOI: 10.1667/0033-7587(2002)158[0352:ioaref]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Radiofrequency Electromagnetic Field on Cardiovascular and Hormonal Parameters of the Autonomic Nervous System in Healthy Individuals

Abstract: The potential health risks of radiofrequency electromagnetic fields (EMFs) emitted by mobile phones are of considerable public interest. The present study investigated the hypothesis, based on the results of our previous study, that exposure to EMFs can increase sympathetic vasoconstrictor activity. Forty healthy young males and females underwent a single-blind, placebo-controlled protocol once on each of two different days. Each investigation included successive periods of placebo and EMF exposure, given in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 19 publications
4
53
0
6
Order By: Relevance
“…For all heart rate parameters, no significant effects were detected under exposure to the field compared to placebo condition. Thus, under the given experimental conditions, autonomic control of heart rate was not affected by weak pulsed high frequency EMF, which was a conclusion others have also reached [Braune et al, 2002].…”
Section: Electroencephalography and Evoked Responsessupporting
confidence: 77%
“…For all heart rate parameters, no significant effects were detected under exposure to the field compared to placebo condition. Thus, under the given experimental conditions, autonomic control of heart rate was not affected by weak pulsed high frequency EMF, which was a conclusion others have also reached [Braune et al, 2002].…”
Section: Electroencephalography and Evoked Responsessupporting
confidence: 77%
“…An exception to this absence of cardiovascular effect may be in the case of exposure to UWB band RFEMF. Recent human experimental studies have produced equivocal results regarding RFEMF exposure and measured blood pressure in normal human experimental studies, but the most recent publication has neither demonstrated nor confirmed any effect [Braune et al, 2002]. However, in all considerations of possible effects of RFEMF on homeostasis and regulatory systems, the possibility of interaction or interference with the mechanism on which a therapeutic process depends must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Any such effect could be clinically important but has not yet been studied. However, studies of possible effects of RFEMF exposure on blood pressure do not show any relationship [Braune et al, 1998[Braune et al, , 2002.…”
Section: Renal Hormonesmentioning
confidence: 97%
“…GSM-like RFR effects in vivo have been studied in experimental animals, mostly by applying frequencies and conditions considered to affect humans [Brusick et al, 1998 {rev};Heikkinen et al, 2001;Mausset et al, 2001;Bartsch et al, 2002;Braune et al, 2002;Di Carlo et al, 2002;Testylier et al, 2002]. Based on the different resonant frequencies of humans and rats (1 vs. 10) [Thuery, 1992], the application of fields between 0.8 and 3 GHz on rat experimental models reflects the exposure of human organisms to 80 and 300 MHz, which is far below GSM-like RFR.…”
Section: Discussionmentioning
confidence: 99%